Age of magmatism and alteration of basaltic rocks cored at the base of IODP Site U1513, Naturaliste Plateau, southwestern Australia. Issue 3 (3rd April 2022) - White, L. T.; Forster, M. A.; Tanner, D.; Tejada, M. L. G.; Hobbs, R.; ,
Abstract: An 82.2 m-thick sequence of basaltic rocks was recovered from a deep-sea core on the eastern flank of the Naturaliste Plateau, offshore southwestern Australia during International Ocean Discovery Program (IODP) Expedition 369. The basaltic rocks were cored at the base of IODP Site U1513 and represent the acoustic basement of the Mentelle Basin. The recovered materials consist of subaerial to shallow-water basalt flows interbedded with volcaniclastic beds and cross-cutting dolerite dykes, all of which have been altered to some degree. Existing paleomagnetic data obtained from the overlying sedimentary sequences indicate that the basaltic sequence cored at Site U1513 was deposited before chron M10Nn.1n (which could be as young as 130.9 Ma or as old as 134.2 Ma, depending on the time scale used). Here, we present the results of 40 Ar/ 39 Ar step-heating experiments conducted on whole-rock samples of two basalt flows and six dolerite dykes to provide greater certainty of the timing of magmatism and subsequent alteration. Each sample was also characterised using optical and scanning electron microscopy together with X-ray fluorescence (XRF) and X-ray diffraction (XRD) analyses. The dolerite dykes are the only rocks that were sampled that record a remnant estimate of the primary cooling age of the magmatic event at ca 134 Ma. This magmatism was contemporaneous with rifting that preceded the break-up of Greater India from Australia/Antarctica and is potentially associated with the Greater Kerguelen large igneous province. The basalt flows record younger apparent ages (between 118 and 110 Ma) that cannot represent extrusive ages given their stratigraphic context, as well as older ages obtained from cross-cutting dykes. We interpret the younger apparent ages to reflect a phase of hydrothermal alteration that reset the argon isotopic system. A tectonic reconstruction, which shows the distribution of magmatism associated with the Greater Kerguelen large igneous province, indicates that the earliest phases of magmatism occurred within an ellipse with a NW–SE-oriented long axis. The reconstruction also shows that the Naturaliste Plateau was approximately 500 km from a known source of magmatism at ca 115 Ma. This distance is within the radius of a mantle plume head and indicates that hydrothermal and/or magmatic activity responsible for resetting the argon isotopic system of the dated basalt flows may have been associated with a mantle plume or was otherwise driven by a local source of magmatism that remained active during the Aptian (126.3–113.0 Ma). KEY POINTS: 40 Ar/ 39 Ar dating indicates Naturaliste Plateau magmatism occurred between 141.3 and 130.9 Ma. The basaltic rocks potentially record a phase of hydrothermal alteration at ca 118–110 Ma. Greater Kerguelen large igneous province magmatism occurred within an ellipse with a NW–SE oriented long axis.